Mommy the life and times of Josefa Jara Martinez : the pillar of social work in the Philippines - Velasco, Melandrew T. 1964- (Ramos Peace and Development Foundation, 2006)
" A lasting tribute to the country's first and pioneering professional social worker and mother of First Lady Amelita "Ming" Martinez Ramos."--Publisher's description.